Geographical Determinants and Sacred Topography: Hadhrami Sayyid Migration to Panthalayini and Its Historical-Spatial Impact on Malabar's Islamic Landscape - Muhammed Fatheen Mk (Penerbit Hellow Pustaka, 2025)
This paper examines the historically significant yet understudied geographical dimensions of Hadhrami Sayyid and Sufi migration to Panthalayini near modern-day Quilandi, analyzing how physical geography shaped both settlement patterns and subsequent religious-cultural developments. Panthalayini's distinctive promontory hills and protective rock formations extending into the sea created an ideal natural harbor that positioned it among Malabar's premier ports. This geographical advantage established it as a crucial intermediary station for diverse pilgrimage routes, including those to Adam's Peak in Ceylon and for ships traversing from Iraq to China during the Abbasid era. Drawing upon Fernand Braudel's longue durée approach and Yi-Fu Tuan's concept of topophilia, this study explores how Panthalayini's sacred geography attracted and sustained over thirty Hadhrami Sayyid clans, including the Bafaqeeh, Haddad, Jifree, Saqaaf, and Aidroos families. The research elucidates how monsoon wind patterns—what Pliny the Elder in his Natural History identified as the Western Hippalos winds—functioned as natural mechanisms facilitating migration, with ships from Cape Diyagroos targeting Panthalayini as their destination. These environmental factors created what might be termed